Somatic neural alterations in non-diabetic obesity: a cross-sectional study. Issue 1 (December 2016) - Yadav, Ram; Sharma, Deepak; Yadav, Prakash; Shah, Dev; Agrawal, Kopila; Khadka, Rita; Islam, Md.
Abstract Background Reports on alterations in somatic neural functions due to non-diabetic obesity, a major risk factor for diabetes, are few and still a matter of debate. Nevertheless, to our knowledge, reports lack any comments on the type of somatic nerve fibers affected in non-diabetic obesity. Therefore, this study aimed to find out the alteration in somatic neural functions in non-diabetic obese persons if any. Methods The study was conducted on 30 adult non-diabetic obese persons (mean age 32.07 ± 7.25 years) with BMI > 30 Kg/m2 (mean BMI 30.02 ± 2.89 Kg/m2 ) and 29 age- and sex-matched normal weight controls (mean age 30.48 ± 8.01 years) with BMI: 18–24Kg/m2 (mean BMI 21.87 ± 2.40 Kg/m2 ). Nerve conduction study (NCS) variables of median, tibial and sural nerves were assessed in each subject using standard protocol. The data were compared by Mann Whitney 'U' test. Results In comparison to normal weight persons, obese had lower compound muscle action potential (CMAP) amplitudes of right median [9.09(7.62–10.20) Vs 10.75(8.71–12.2) mV, p  = 0.025] and bilateral tibial nerves [Right: 8.5(7.04–11.18) Vs 12.1(10.55–15) mV, p  < 0.001 and left 9.08(6.58–11.65) Vs 13.05(10.2–15.6) mV, p  = 0.002]. Furthermore, obese persons had prolonged CMAP durations of right and left median [10.5(9.62–12) Vs 10(8.4–10.3) ms, p  = 0.02 and 10.85(10–11.88) Vs 10(9–10.57) ms, p  = 0.019] and right tibial [10(9–11) 8.5(7.92–10) ms, p  = 0.032] nerves. Sensory NCS (sural nerve) also showed diminished sensory nerve action potential (SNAP) amplitude [16(12.08–18.21) vs 22.8(18.3–31.08) μV, p  < 0.001] and prolonged duration. However, onset latencies and conduction velocities for all nerves were comparable between the groups. Conclusion This study documents subclinical peripheral nerve damage in non-diabetic obese with abnormal NCS parameters; shorter amplitudes and prolonged CMAP and SNAP durations. The reduced amplitudes of mixed and sensory nerves might be due to decreased axonal number stimulation or actual decrease in number of axonal fibers, or defect at NMJ in non-diabetic obese. Prolonged durations but normal onset latencies and conduction velocities strongly suggest involvement of slow conducting fibers.